Battery charging and discharging control of a hybrid energy system using microcontroller - Triyanto Pangaribowo; Wahyu Mulyo Utomo; Afarulrazi Abu Bakar; Deni Shidqi Khaerudini (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
This study aims to control charging and discharging the battery for hybrid energy systems. The control system works by selecting the right energy source to supply voltage to the load. And also this control system can regulate charging and discharging the battery automatically. The voltage source consists of two energy, namely from the battery and DC source. The control system that has been designed has the ability to choose the right DC source when the battery capacity is less than 80%. This system also has a good ability to choose a battery source when the battery reaches 100% capacity and the DC source has a voltage drop of more than 20%. This control system is equipped with excessive electric current protection so that the security level is high.